2009
DOI: 10.1523/jneurosci.5667-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of the 2B Subunit of the NMDA Receptor Is Necessary for Taste Memory Formation

Abstract: We aimed to test whether tyrosine phosphorylation of the NMDA receptor (NMDAR) in the insular cortex is necessary for novel taste learning. We found that in rats, novel taste learning leads to elevated phosphorylation of tyrosine 1472 of the NR2B subunit of the NMDAR and increases the interaction of phosphorylated NR2B with the major postsynaptic scaffold protein PSD-95. Injection of the tyrosine kinase inhibitor genistein directly into the insular cortex of rats before novel taste exposure prevented the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…This hypothesis is substantiated by our biochemical observations indicating, in THYTau22 mice, both reduced Y1472-NR2B phosphorylation and abnormal interaction of NR2B with Tau. Previous work indicated that Y1472-NR2B phosphorylation modulates NMDAR function and is critical for memory formation (Mizuno et al, 2003;Barki-Harrington et al, 2009). Its reduction in Tau mice might thus be related to memory impairments seen using the MWM task.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis is substantiated by our biochemical observations indicating, in THYTau22 mice, both reduced Y1472-NR2B phosphorylation and abnormal interaction of NR2B with Tau. Previous work indicated that Y1472-NR2B phosphorylation modulates NMDAR function and is critical for memory formation (Mizuno et al, 2003;Barki-Harrington et al, 2009). Its reduction in Tau mice might thus be related to memory impairments seen using the MWM task.…”
Section: Discussionmentioning
confidence: 97%
“…With the development of mass spectroscopy and phosphorylation-specific antibodies over the last two decades, several tyrosine sites within the carboxyl terminus of the GluN2B subunit have been identified as substrates of Src family kinases (14 -16). A major tyrosine site on GluN2B, Tyr-1472, has been reported to control the trafficking of GluN2B-containing NMDARs and may be involved in such processes as synaptic plasticity, memory, and pain (17)(18)(19)(20). However, the roles of other tyrosine sites on GluN2B remain to be explored.…”
Section: N-methyl-d-aspartate Receptors (Nmdars)mentioning
confidence: 99%
“…Three main paradigms are used in the context of taste learning: incidental taste learning (novel taste), conditioned taste aversion (CTA), and latent inhibition of CTA (LI-CTA), in all of which the molecular and neural substrates are well defined (Elkobi et al 2008;Barki-Harrington et al 2009;Gal-Ben-Ari and Rosenblum. 2011).…”
Section: Translation Regulation In the Cortex: The Taste Casementioning
confidence: 99%